Negative Role of the Environmental Endocrine Disruptors in the Human Neurodevelopment - Roncati, Luca; Termopoli, Veronica; Pusiol, Teresa (Frontiers in Neurology, 2016)
The endocrine disruptors (EDs) are able to influence the endocrine system, mimicking or antagonizing hormonal molecules. They are bio-persistent for their degradation resistance in the environment. Our research group has investigated by gas chromatography-mass spectrometry (GC-MS) the EDs presence in 35 brain samples, coming from 27 cases of sudden intrauterine unexplained death syndrome (SIUDS) and 8 cases of sudden infant death syndrome (SIDS), collected by centralization in the last year (2015). More in detail, a mixture of 25 EDs has been subjected to analytical procedure, following standard protocols. Among the target analytes, some organochlorine pesticides (OCPs), that is α-chlordane, γ-chlordane, heptachlor, p,p-DDE, p,p-DDT, and the two most commonly used organophosphorus pesticides (OPPs), chlorpyrifos and chlorfenvinfos, have been found in 7 and 3 samples, respectively. The analytical procedure used to detect the presence of environmental EDs in cortex samples has been successfully implemented on SIUDS and SIDS victims. The environmental EDs have been found to be able to overcome the placental barrier, reaching also the basal ganglia assigned to the control of the vital functions. This finding, related to the OPPs bio-persistence, implies a conceptual redefinition of the fetal-placental and fetal blood-brain barriers: not real safety barriers, but simply time-deferral mechanisms of absorption.